Research on inspection method of metalens based on phase-shifting interference - Wei-Han Li; Zhi-Hao Wang; Cheng-Gang Mo; Yong-Bo Deng; Cheng-Miao Wang; Yu Jiao; Yang Gao; Si-Yuan Yao; Xiaokun Wang; Xin Zhang; Liang Miao; Xin-Dong Chen (Results in Physics, 2024)
With the ultra-thin thickness and excellent performance, metalens are bi-dimensional optical elements composed of nanopatterned structures that demonstrate significant potential for various applications such as holography, planar imaging and tomography. However, the small size of metalens makes it challenging to precisely quantify their wavefront aberration, thus impeding their broader utilization. To address this challenge, we propose an innovative method for measuring wavefront aberration in metalens using phase-shift interferometry. Furthermore, we have developed the Small Aperture Interferometric Imaging Detection System with variable fields of view, specifically designed for metalens. This system can accurately measure the wavefront aberration of metalens with different fields of view with PV accuracy of 1/20λ, further enabling the acquisition of imaging performance parameters, including Modulation Transfer Function (MTF) and Point Spread Function (PSF). This innovative measurement approach not only enables quantitative evaluation of performance of metalens but also assists designers and manufacturers in optimizing process flows and identifying potential defects. As a result, this approach aids in promoting the industrial application of metalens.